Operative technique for reconstruction of distal ulna after giant cell tumour resection - Katarina Barbarić Starčević; Ivan Bohaček (Acta Clinica Croatica, 2023)
Giant cell tumour (GCT) is a rare, benign tumour, but it has a locally aggressive nature and a high rate of recurrence. A wide en-bloc resection of the distal part of the ulna, with or without stabilisation of the ulnar stump, is the recommended treatment option. Functional results after that kind of surgery are mostly satisfying but, in some cases, it can result in wrist instability, causing pain and weakness of grip strength. That is why when it comes to young people, with high functional demands, we prefer reconstruction of distal ulna and distal radioulnar joint after an en-bloc resection of the distal ulna. The distal ulna is reconstructed with an autologous free fibular graft and the distal radioulnar joint is stabilised with an autologous palmaris longus tendon graft. We present our operative technique and good functional results of three young patients treated with this procedure. Our results confirm the hypothesis that the reconstruction of the distal ulna and the distal radioulnar joint leads to a satisfactory functional result in young and active patients with higher functional demands.